Transepithelial versus epithelium-off crosslinking in adults with progressive keratoconus - TOKER, AYŞE EBRU; ÇERMAN, EREN (ELSEVIER SCIENCE INC, 2015)
PURPOSE: To compare the efficacy of epithelium-off corneal collagen crosslinking (CXL) with transepithelial CXL in patients with progressive keratoconus. SETTING: Department of Ophthalmology, Marmara University School of Medicine, Istanbul, Turkey. DESIGN: Retrospective cohort study. METHODS: Eyes that had transepithelial CXL were compared with eyes treated with epithelium-off CXL. All patients with a follow-up of 18 months were evaluated for uncorrected (UDVA) and corrected (CDVA) distance visual acuities, corneal topography, aberrometry, and pachymetry (Pentacam). RESULTS: The mean patient age was 22.8 years +/- 4.7 (SD) (range 18 to 31 years) in the transepithelial group (30 eyes) and 23.7 +/- 3.9 years (range 18 to 30 years) in the epithelium-off group (30 eyes). The mean UDVA and CDVA significantly improved in both groups (P < .001). There was no significant difference in the CDVA gain between the 2 groups. In the epithelium-off group, significant improvements occurred in spherical error (P = .002), spherical equivalent (P = .004), maximum keratometry (K), flat K (P = .036), and steep K (P < .001). The reductions in flat K, steep K, and maximum K were greater in the epithelium-off group (P = .004 for flat K; P < .001 for steep K and maximum K). In the transepithelial group, significant improvements occurred in the cylindrical error (P = .009) and in the index of surface variance and index of surface asymmetry (both P < .001). CONCLUSION: Although transepithelial CXL seemed to have reduced effectiveness in inducing improvement in topographic indices, its effect on visual acuity is likely to be similar to that of epithelium-off CXL.
Keywords: ULTRAVIOLET-A LIGHT; RIBOFLAVIN CONCENTRATION; CORNEAL TOPOGRAPHY; IONTOPHORESIS; KERATITIS; CXL